2013
DOI: 10.1074/jbc.m112.371732
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Small Molecule Inhibitor of Plasminogen Activator Inhibitor Type 1 That Accelerates the Transition into the Latent Conformation

Abstract: Background: Inhibition of PAI-1 may yield beneficial effects in e.g. cardiovascular diseases and cancer. Results: The small molecule PAI-1 inhibitor, AZ3976, binds latent but not active PAI-1. The structure of the AZ3976⅐latent PAI-1 complex is presented. Conclusion: AZ3976 inhibits PAI-1 by accelerating latency transition, presumably by binding a prelatent form of PAI-1. Significance: This study provides new drug design opportunities for PAI-1 inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 61 publications
1
34
0
Order By: Relevance
“…Directed mutagenesis showed that annonacinone binds to the pocket between s2A, hD and hE similarly to other small molecule PAI-1 inhibitors such as tiplaxtinin, AZ3976 and embelin141517. Molecular dynamics is in agreement with site directed mutagenesis results.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Directed mutagenesis showed that annonacinone binds to the pocket between s2A, hD and hE similarly to other small molecule PAI-1 inhibitors such as tiplaxtinin, AZ3976 and embelin141517. Molecular dynamics is in agreement with site directed mutagenesis results.…”
Section: Discussionsupporting
confidence: 75%
“…Docking studies together with mutagenesis localized its binding site in the region of helices D and E close to the vitronectin binding site14. Three crystal structures of latent PAI-1 cocrystallized with compound AZ397615 and active PAI-1 cocrystallized with compound CDE-09616 and Embelin17 were also reported. They show different binding site on PAI-1 and different mechanism of action.…”
mentioning
confidence: 98%
“…(B), comparison of the AZ3976 (56) binding site in ligand bound and free latent PAI-1. From Fjellstrom et al [97]. (For interpretation of the references to color in this figure legend, the reader is referred to the web version of this article.)…”
Section: Embelin (57)mentioning
confidence: 97%
“…Physiologically, this regulation is achieved by binding to the cell adhesion factor vitronectin, leading to an ∼50% increase in the active state t 1/2 (3). Because high levels of active PAI-1 are associated both with poor prognoses for some cancers, presumably due to interactions with vitronectin, and with cardiovascular diseases (1), PAI-1 inhibitors that accelerate the latency transition are under development (1,4,5). However, drug design efforts are hampered by the lack of detailed molecular mechanisms for PAI-1 conformational changes.…”
mentioning
confidence: 99%